Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Mendsho Tangerang Selatan - Pirdaus, Gifar; Liawati Liawati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Employee Performance at PT MENDSHO, South Tangerang, both partially and simultaneously. This research uses a quantitative approach. The data collection method employed was a questionnaire, with a population of 66 respondents. The data analysis techniques used included validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of the study based on the t-test showed that for the Work Discipline variable, the t-value > t-table (7.743 > 1.99773) with a significance level of 0.000 < 0.05. Thus, H0 is rejected and H1 is accepted, meaning that Work Discipline (X1) partially has a significant effect on Employee Performance (Y). For the Work Environment variable, the t-value > t-table (5.786 > 1.99773) with a significance level of 0.000 < 0.05. Thus, H0 is rejected and H2 is accepted, meaning that Work Environment (X2) partially has a significant effect on Employee Performance (Y). Meanwhile, based on the F-test, the F-value > F-table (89.619 > 3.143) with a significance level of 0.000 < 0.05. Therefore, H0 is rejected and H3 is accepted, indicating that Work Discipline (X1) and Work Environment (X2) simultaneously have a significant effect on Employee Performance (Y) at PT MENDSHO, South Tangerang. The coefficient of determination obtained is 74.3%, while the remaining 25.7% is influenced by other factors Keywords: Work Discipline, Work Environment, Employee Performance